Emerging adults’ meanings and scripts of virginity and virginity loss - Brown, Katlin (Kansas State University, 2023)
Understandings of virginity loss experiences can influence virginity loss experiences, sexual identity construction, sexual agency, and general aspects of sexual well-being. Emerging adults, those 18 to 29 years old, are in a life stage in which exploring sexual and romantic relationships are a key aspect of their identity construction. However, there is limited research addressing what meanings of virginity emerging adults’ hold and how they differ among them. The following two-part study aimed to examine the meaning of virginity and virginity scripts of college-attending emerging adults, and how they may differ. Guided by sexual script theory (Simon & Gagnon, 1986) and a feminist critique framework (Osmond & Thorne, 1993), part-one of this study, used qualitative data to identify meanings/significance of virginity held by emerging adults. Using direct content analysis, nine codes were identified as providing emerging adults’ current meanings of virginity/virginity loss, (1) no significance, (2) waiting until marriage, (3) right partner or right time, (4) purity, (5) religion provides meaning, (6) entwined or bonded souls, (7) sexual milestone, (8) significant but no context, and (9) social construct/double standard. A tenth and unexpected code, changes in meaning, represented a process of change in their meaning/significance due to a variety of factors. Gender comparisons of whether or not the code was expressed by cisgender men and cisgender women were made; however, no differences were found. In part two of this study, we used quantitative methods to examine identified virginity scripts (i.e., gift, stigma, process) of emerging adults and whether they differ by sexual orientation, gender, religiosity, and sexual experience. While no gender differences were found, relationships between sexual orientation, sexual experience, and religiosity and script endorsement were found. These findings suggest that emerging adults hold a variety of meanings of virginity, as well as specific factors contributing to the meanings and conceptions of virginity. Establishing healthy conceptions of virginity/virginity loss can potentially contribute to decreasing gender inequities within the realm of sexuality (e.g., sexual double standard). These findings can inform sex education curriculums in terms of being aware and presenting multiple meanings of first sex, while sex researchers can work to avoid making assumptions about one’s meaning or significance of virginity. Future research related to sexual well-being and relationships among this population should be pursued, in addition to seeking out diverse samples.
Keywords: Emerging adults; Virginity beliefs; Feminist critique framework; College students; Virginity loss scripts